Intersecting Epidemics: Intimate Partner Violence, Stress, and Diabetes Among South Asian Women in the United States - Newton, Bailey; Nagaraj, Nitasha; Vyas, Amita (Journal of Public Health International, 2025)
South Asian women in the United States face disproportionate health challenges, including higher rates of intimate partner violence as well as higher rates of Type 2 diabetes and gestational diabetes compared to other racial and ethnic groups. This cross-sectional study examines the association between intimate partner violence (psychological, physical, and sexual) and the diagnosis of gestational diabetes and type 2 diabetes. A web-based survey recruited 2,634 South Asian women in the U.S., collecting data on socio-demographics, intimate partner violence experiences, stress levels, and diabetes diagnosis. Logistic regression models adjusted for significant sociodemographic factors revealed that women with a history of intimate partner violence were 5.82 significantly more likely to report a type 2 diabetes diagnosis and 3.91 more likely to report a gestational diabetes diagnosis. Furthermore, stress as measured by the perceived stress scale, was also higher among women with intimate partner violence, potentially moderating the relationship between intimate partner violence and adverse health outcomes through cortisol dysregulation. Despite high levels of educational attainment and employment, the prevalence of intimate partner violence was alarmingly high (66.7%), highlighting its pervasive impact on socioeconomic strata. These findings underscore the urgent need for culturally tailored interventions addressing intimate partner violence and its health consequences within South Asian communities. Further research is warranted to elucidate causal pathways and inform integrated public health strategies to mitigate disparities in chronic disease and intimate partner violence-related health outcomes.
Keywords: South Asian; women; intimate partner violence; type II diabetes; gestational diabetes